Pyridinic and pyrrolic nitrogen-enriched carbon as a polysulfide blocker for high-performance lithium–sulfur batteries. Issue 4 (6th March 2019) - Zhang, Kailong; Wang, Li; Cai, Wenlong; Chen, Li-Feng; Wang, Di; Chen, Yuehan; Pan, Honglin; Wang, Liangbiao; Qian, Yitai
Abstract : Pyridinic and pyrrolic nitrogen (16.95 atm%)-enriched carbon was simply prepared as an interlayer constructed in Li–S batteries. Abstract : Pyridinic and pyrrolic nitrogen-enriched carbon (CN x ) with a high content of 16.95 atm% was simply prepared as an interlayer in Li–S batteries. For largely improving the electrochemical performance, it retarded the shuttle effect of polysulfides by chemical (main) and physical interactions. As a result, the as-constructed Li–S batteries with CN x still delivered a capacity of 730 mA h g −1 after 500 cycles at 1C with nearly 100% coulombic efficiency. When the mass loading of sulfur increased to 5 mg cm −2, the assembled Li–S battery also exhibited excellent electrochemical performance with a capacity of 4.57 mA h cm −2 at 0.1C after 40 cycles.